2006
DOI: 10.1111/j.1366-9516.2005.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene fragmentation of Amazon species’ ranges

Abstract: Historical patterns of connection and isolation of the impressive biological diversity of the Amazon Basin have been the subject of extensive debate, based on evidence drawn from distributional patterns of endemic species, vegetation histories from palynological studies, and geological studies. We develop species-specific ecological niche models based on current occurrence patterns of 17 species of birds and woody plants, which we project onto modelled Pleistocene (Last Glacial Maximum) climatic patterns to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 50 publications
(78 reference statements)
4
63
0
2
Order By: Relevance
“…Our paleodistributional reconstructions concur with those of prior ENM-based studies indicating LGM expansion of cerrado and other dry-habitat biomes (Collevatti et al 2012, Bonatelli et al 2014), as well as those which identified LGM barriers for forest that coincide with our reconstructed dispersal corridors for a non-forest species (Bonaccorso et al 2006, Peterson andNyá ri 2008). Although projections from niche modeling algorithms presently provide only a single, generalized snapshot of climatic suitability for a given time slice, they illuminate processes affecting the broader distributional potential of C. durissus since the LIG.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our paleodistributional reconstructions concur with those of prior ENM-based studies indicating LGM expansion of cerrado and other dry-habitat biomes (Collevatti et al 2012, Bonatelli et al 2014), as well as those which identified LGM barriers for forest that coincide with our reconstructed dispersal corridors for a non-forest species (Bonaccorso et al 2006, Peterson andNyá ri 2008). Although projections from niche modeling algorithms presently provide only a single, generalized snapshot of climatic suitability for a given time slice, they illuminate processes affecting the broader distributional potential of C. durissus since the LIG.…”
Section: Discussionsupporting
confidence: 78%
“…Availability of climatic reconstructions for the Pleistocene allows exploration of paleo-distributional potential of species, including the location and timing of range disjunctions and potential dispersal routes. Although previous ENM studies of Amazon Basin biotas have indicated that distributions of forest species did fragment owing to climate changes (Bonaccorso et al 2006, Peterson andNyá ri 2008), few have reconstructed the converse phenomenon of broadened distributions of savannah species (Bonaccorso et al 2006, Collevatti et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypetheliaceae also show a marked bias in area-based diversity towards the Neotropics, a pattern not observed in Graphidaceae, which are equally diverse in well-preserved rainforest biomes across the tropics, specifically in the Neotropics and tropical Asia (Lücking et al 2014a). The reason for this bias is unknown, but it could be related to the unique diversity of the family in biomes outside rainforests, since palaeoclimatic fluctuations have led to frequent changes in the mosaic-like distribution of rainforest and savannah-like vegetation, especially in South America ( Van der Hammen 1974;Meave & Kellmann 1994;Pennington et al 2000;Bonaccorso et al 2006;Flenley 2013). Further study is required to validate our assumption of species richness being generally twice as high in the Neotropics compared to the Palaeotropics, as it is based on limited results from four presumably well-sampled grids.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, because molecular clocks are frequently calibrated based on fossil information, insights from these two sources of information are generally non-independent, but give the appearance of independent confirmation. Nonetheless, very preliminary analyses using paleoclimatic projections of niche models are casting doubt on issues that had been "decided" based on molecular data, such as the pre-Pleistocene nature of vertebrate speciation in the Amazon Basin (Bonaccorso et al 2006;Peterson and Nyári 2007) and the exceptional age of the Sahara Desert as a biogeographic barrier (Nyári et al 2010). Figure 3 illustrates one such effort to reconstruct historical (Pleistocene Last Glacial Maximum) ranges of species, for Schiffornis turdinus, a bird species of the Neotropical lowlands .…”
Section: Niche Modeling Insightsmentioning
confidence: 99%